Gallium-68 radiolabeling of biomolecules for positron emission tomography with special reference to imaging of inflammation and bone - Käkelä, Meeri (fi=Turun yliopisto|en=University of Turku|, 2020)
Positron emission tomography (PET) radiopharmaceuticals are composed of a positron emitting radionuclide (e.g. gallium-68) and a molecular structure. MicroRNA-21 is a relevant target overexpressed in many diseases, such as osteoporosis and osteosarcoma. Interference of microRNA-21 by anti-microRNA-21 would be a potential medicinal treatment. 3′-NOTA-chelated anti-microRNA-21 was radiolabeled with gallium-68 using the fractionated method and mixed with 5′-alendronate-conjugated microRNA-21. 68Ga-labeled double helix was formed rapidly at room temperature. The double helix thus formed was in vivo PET imaged to evaluate whether its bone accumulation was increased because of conjugated bis(phosphonate). PET imaging revealed that bis(phosphonate)-conjugated anti-microRNA-21 accumulates in the bone. This observation can be utilized in the future when developing medicinal treatments for diseases involving micro-RNA-21. Sialic acid-binding immunoglobulin-like lectin-9 (Siglec-9) is a leukocyte ligand of vascular adhesion protein-1 (VAP-1). VAP-1 plays an important role in many inflammatory conditions. Inflammation has s signicifant part in a number of diseases, such as atherosclerosis and diabetes. PET imaging provides tools for studying the mechanisms related to the process of inflammation and to discover potential targeted therapeutics. [68Ga]Ga-DOTA-Siglec-9 can be used as a PET tracer for imaging of inflammation. The purpose of this thesis was to develop an automated protocol for producing GMP-grade inflammation imaging agent [68Ga]Ga-DOTA-Siglec-9 for first-inhuman studies. This GMP-grade tracer was produced using a fully automated acetone-based method. It was concluded that this method facilitates efficient production of GMP-grade [68Ga]Ga-DOTA-Siglec-9 and the tracer is suitable for human use.